Development of camelid single chain antibodies against Shiga toxin type 2 (Stx2) with therapeutic potential against Hemolytic Uremic Syndrome (HUS). - Mejias, María Pilar (2016)
Shiga toxin (Stx)-producing Escherichia coli (STEC) infections are implicated in the development of the life-threatening Hemolytic Uremic Syndrome (HUS). Despite the magnitude of the social and economic problems caused by STEC infections, no licensed vaccine or effective therapy is presently available for human use. Single chain antibodies (VHH) produced by camelids exhibit several advantages in comparison with conventional antibodies, making them promising tools for diagnosis and therapy. In the present work, the properties of a recently developed immunogen, which induces high affinity and protective antibodies against Stx type 2 (Stx2), were exploited to develop VHHs with therapeutic potential against HUS. We identified a family of VHHs against the B subunit of Stx2 (Stx2B) that neutralize Stx2 in vitro at subnanomolar concentrations. One VHH was selected and was engineered into a trivalent molecule (two copies of anti-Stx2B VHH and one anti-seroalbumin VHH). The resulting molecule presented extended in vivo half-life and high therapeutic activity, as demonstrated in three different mouse models of Stx2-toxicity: a single i.v. lethal dose of Stx2, several i.v. incremental doses of Stx2 and intragastrical STEC infection. This simple antitoxin agent should offer new therapeutic options for treating STEC infections to prevent or ameliorate HUS outcome.